2016
DOI: 10.17265/1548-6583/2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Are IFRS Harder to Implement for Emerging Economies Compared to Developed Countries? A Literature Review

Abstract: In practice, the international accounting harmonization process faces cultural resistance in the concrete situations of accounting reforms. We often tend to believe that this resistance is felt more in the so-called emerging countries, rather than the developed ones. It is precisely this idea that the paper attempts to analyze, based on a literature review. The literature shows that emerging countries do not have the infrastructure or the real needs justifying a reform of international harmonization, except th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Market issues: Raoudha (2016), Jones andFinley, 2011, Ballas et al, 2010 proved that since IFRS requires the measurement of the assets and liabilities of enterprises at market value at the reporting time, the market needs to be relatively developed be able to provide reliable information. Samaha andKhlif (2016) andATU et al, (2016) conducted studies in undeveloped and developing countries and found that the capital markets, financial markets were developing, and certain financial instruments such as convertible bonds, derivatives, preferred stocks have not been widely traded in the market.…”
Section: Legal Issuesmentioning
confidence: 99%
“…Market issues: Raoudha (2016), Jones andFinley, 2011, Ballas et al, 2010 proved that since IFRS requires the measurement of the assets and liabilities of enterprises at market value at the reporting time, the market needs to be relatively developed be able to provide reliable information. Samaha andKhlif (2016) andATU et al, (2016) conducted studies in undeveloped and developing countries and found that the capital markets, financial markets were developing, and certain financial instruments such as convertible bonds, derivatives, preferred stocks have not been widely traded in the market.…”
Section: Legal Issuesmentioning
confidence: 99%
“…Kilic et al (2014) believed that IFRS applied in underdeveloped countries would help to reduce fraud when preparing financial statements because there were still some arbitrary and sensual feelings in the national standards. Raoudha (2016) felt that the biggest challenge when applying IFRS was to implement regulations on accountability and disclosure and determining the fair value of the market in emerging countries.…”
Section: IVmentioning
confidence: 99%